2006
DOI: 10.1128/aem.72.1.932-936.2006
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Transformable Acinetobacter sp. Strain ADP1 Belongs to the Newly Described Species Acinetobacter baylyi

Abstract: Genotypic and phenotypic analyses were carried out to clarify the taxonomic position of the naturally transformable Acinetobacter sp. strain ADP1. Transfer tDNA-PCR fingerprinting, 16S rRNA gene sequence analysis, and selective restriction fragment amplification (amplified fragment length polymorphism analysis) indicate that strain ADP1 and a second transformable strain, designated 93A2, are members of the newly described species Acinetobacter baylyi. Transformation assays demonstrate that the A. baylyi type s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(95 citation statements)
references
References 25 publications
3
91
0
1
Order By: Relevance
“…This bacterium has high competency for natural transformation [32] and occasionally causes antibioticresistant infections in humans [33]. No plasmids or viruses are present in our experimental strains and therefore the only mechanism of recombination is transformation.…”
Section: Introductionmentioning
confidence: 99%
“…This bacterium has high competency for natural transformation [32] and occasionally causes antibioticresistant infections in humans [33]. No plasmids or viruses are present in our experimental strains and therefore the only mechanism of recombination is transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the naturally transformable Acinetobacter sp. ADP1 strain and its derivative BD413 were shown to belong to the newly described species Acinetobacter baylyi (Vaneechoutte et al, 2006). This strain can be transformed efficiently with DNA of different sources.…”
Section: Natural Transformationmentioning
confidence: 99%
“…The exogenous isolation of MGEs, which was originally used to retrieve plasmids from river epilithon (Bale et al, 1988), was also successfully used to capture MGEs from soil or phytosphere communities (Smalla and Sobecky, 2002). Recipients functioning as a genetic sink, and introduced under laboratory or in situ conditions, have acquired MGEs conferring selectable traits such as mercury or antibiotic resistance from the bacterial fraction of bulk or rhizosphere soil (Drønen et al, 1998;Heuer and Smalla, 2007;Heuer et al, 2002;van Overbeek et al, 2002). Mercury resistance was used as an effective selective marker to exogenously isolate self-transferable plasmids from the phytosphere of different crops in Gram-negative recipients (Lilley and Bailey, 1997;Lilley et al 1994;Schneiker et al, 2001;Smit et al, 1998) or from mercury-polluted soils (Drønen et al, 1998).…”
Section: Mges In Bacterial Communities Of Agricultural Settings Prevamentioning
confidence: 99%
See 1 more Smart Citation
“…The state of competence leading to natural transforma-bility is commonly related to the presence of competence genes, like the com genes present in Thermus thermophilus and Acinetobacter baylyi (Friedrich et al, 2001 and. The naturally transformable strain A. baylyi ADP1 (ADP1; also known as A. baylyi BD413, see Vaneechoutte et al, 2006) has been demonstrated to develop genetic competence and to be transformable in soil (Ceccherini et al, 2003;Kay et al, 2003;Nielsen et al, 2000b). Transformants successfully occurred after treatment with DNA homologous to recipient genomes (Nielsen et al, 2000a).…”
Section: Introductionmentioning
confidence: 99%